PENGEMBANGAN LITERASI BACA DI MI MISBAHUL QURO’ MENGGUNAKAN METODE BACA GAMBAR - Evi Dwi Kartikasari; Titik Khotiah; Indah Nurul Ma’rufah; Fery Arianto; Himawan Arsy; Anggie Lintang Mawarni (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Reading is an important activity in the teaching and learning process. We can find out information by reading, and we can broaden our insight and think critically. Without reading, we cannot know what is happening in the world, and we cannot know the knowledge that exists in the world, therefore the Importance of a Literacy Culture in Schools To increase reading interest in Indonesian society, we usually start from school. The approach in this study was qualitative research using descriptive methods, while the data collection process used interview and observation techniques. The development of children's literacy at the Madrasah Ibtidaiyah Misbahul Quro', Dusun Kepudiwetan, Kepudinegara Village, was managed by the library and collaborating with class teachers was less effective. Literacy development is rarely carried out outside class hours, and is only carried out during the learning process. The role of KKN 2 ITBAD Lamongan students is to support the development of reading literacy at Madrasah Ibtidaiyah Misbahul Quro'. Reading literacy development activities by KKN 2 ITBAD Lamongan at MI MISBAHUL QURO'' Kepudiwetan have been able to improve the development of reading literacy among Madrasah Ibtidaiyah students as an effort to support the existence of an international literacy movement. It is hoped that the realization of developing reading literacy using the picture reading method can foster a culture of love of literacy.